Mutation-targeted therapy with sunitinib or everolimus in patients with advanced low-grade or intermediate-grade neuroendocrine tumours of the gastrointestinal tract and pancreas with or without cytoreductive surgery: protocol for a phase II clinical trial. Issue 5 (19th May 2015) - Neychev, Vladimir; Steinberg, Seth M; Cottle-Delisle, Candice; Merkel, Roxanne; Nilubol, Naris; Yao, Jianhua; Meltzer, Paul; Pacak, Karel; Marx, Stephen; Kebebew, Electron
Abstract : Introduction: Finding the optimal management strategy for patients with advanced, metastatic neuroendocrine tumours (NETs) of the gastrointestinal tract and pancreas is a work in progress. Sunitinib and everolimus are currently approved for the treatment of progressive, unresectable, locally advanced or metastatic low-grade or intermediate-grade pancreatic NETs. However, mutation-targeted therapy with sunitinib or everolimus has not been studied in this patient population. Methods and analysis: This prospective, open-label phase II clinical trial was designed to determine if mutation-targeting therapy with sunitinib or everolimus for patients with advanced low-grade or intermediate-grade NETs is more effective than historically expected results with progression-free survival (PFS) as the primary end point. Patients ≥18 years of age with progressive, low-grade or intermediate-grade locally advanced or metastatic NETs are eligible for this study. Patients will undergo tumour biopsy (if they are not a surgical candidate) for tumour genotyping. Patients will be assigned to sunitininb or everolimus based on somatic/germline mutations profile. Patients who have disease progression on either sunitinib or everolimus will crossover to the other drug. Treatment will continue until disease progression, unacceptable toxicity, or consent to withdrawal. Using the proposed criteria, 44 patients will be accrued within each treatment group during a 48-month period (a total of 88 patients for the 2 treatments), and followed for up to an additional 12 months (a total of 60 months from entry of the first patient) to achieve 80% power in order to test whether there is an improvement in PFS compared to historically expected results, with a 0.10 α level one-sided significance test. Ethics and dissemination: The study protocol was approved by the institutional review board of the National Cancer Institute (NCI-IRB Number 15C0040; iRIS Reference Number 339636). The results will be published in a peer-reviewed journal and shared with the worldwide medical community. Trial registration number: NCT02315625.